Effect of cues of observability on dishonest behaviour: an experimental research - Enyan, Olivia (2023)
Holding private information often gives individuals an incentive to engage in dishonest acts such as cheating or misreporting that information during economic decision making. There has been a large and growing body of experimental research which has analysed dishonest behaviour over the past decade. Though the experimental literature on dishonest behaviour continues to grow but there are pending questions on what trigger and discourage cheating.